2020
DOI: 10.1111/jorc.12317
|View full text |Cite
|
Sign up to set email alerts
|

Associations between materials used and work‐related musculoskeletal hand complaints among haemodialysis nurses

Abstract: SUMMARYBackgroundOne in every two haemodialysis nurses has reported musculoskeletal complaints concerning their hands, which is twice that reported for hospital nurses in general. It is possible that there is an association between the materials used by haemodialysis nurses and the occurrence of hand complaints.ObjectivesTo examine the association between the type of dialysis machine and disposables used with the occurrence of hand complaints among haemodialysis nurses. To compare occupational risks of develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The experienced resistance when opening and closing the clamps on the bloodlines was described by the haemodialysis nurses' as giving discomfort or pain in the thumbs and fingers. Although the nurses expressed potential differences between various manufacturers, in the study by Westergren et al [10], no significant differences in the number of clamping grips used were found. Similarly, the act of connecting the patient's access to the dialysis machine's bloodlines also generates a certain resistance with the rotational movements.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The experienced resistance when opening and closing the clamps on the bloodlines was described by the haemodialysis nurses' as giving discomfort or pain in the thumbs and fingers. Although the nurses expressed potential differences between various manufacturers, in the study by Westergren et al [10], no significant differences in the number of clamping grips used were found. Similarly, the act of connecting the patient's access to the dialysis machine's bloodlines also generates a certain resistance with the rotational movements.…”
Section: Discussionmentioning
confidence: 89%
“…It suggests that an emphasis should be placed on preventing priming related hand complaints when designing and planning the daily workflow. Previous research has revealed that there is a significant difference in the required number of twisting/turning movements performed during the priming procedures with the different machine types, but this does not seem to have a relationship to the development of hand complaints among haemodialysis nurses [10]. An attention-grabbing finding derived from the reflective dialogue was that the exact site(s) of the hand complaint(s) varied depending on which dialysis machine was used.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Patients are getting more involved (de Kleijn et al, 2020 ) and for each patient who prepares their own machine, the number of hand twists/turns that a nurse needs to make during machine preparation will decrease. The number of hand twists/turns saved depends on the machine type used (Westergren et al, 2020 ). Still, every twist counts, as work tasks performed more than ten times a day increase the risk of developing work‐related musculoskeletal problems (Serranheira et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main stressors are time management, treatment complications/emergencies and technical problems (Karkar et al, 2015 ; Vioulac et al, 2016 ), but coping with patient deaths is also associated with high levels of stress (Lee & King, 2014 ). Further, the materials needed for providing treatments to patients are assumed to contribute to the high prevalence of musculoskeletal complaints among haemodialysis nurses (Westergren & Lindberg, 2022 ; Westergren et al, 2020 ). To protect their wellbeing, haemodialysis nurses develop several coping strategies (Cousins et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%